Pemerolehan Fonologi Dalam Perkembangan Bahasa Anak Usia 3,5 Tahun - Testin Gulo; Ihsan Hidayatulloh; Basilius B. Gulo (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2023)
Phonological acquisition is a critical aspect of a child's language development. This process involves the formation of a complex sound system of language through the interaction between genetic and environmental factors. This article examines how the process of phonological acquisition in the language of children aged 3.5 years. Children who were the object of this study had a fairly good level of language acquisition. But in terms of phonology, there are still many errors in pronunciation. The background of this study examines the importance of understanding the phonological acquisition process in a critical stage of children's language development. The study aims to identify the main factors that influence phonological acquisition in this age range. The method used in this study is a descriptive qualitative method, which explains the acquisition of language in children in terms of phonology. Data collection techniques involve listening, interacting and speaking. The object of this study was a girl named Grace Angel Agata, who in interacting have been able to pronounce various forms of simple words and sentences. The results showed that the children were able to pronounce vowel elements (a, i, u, e, o), while consonant elements were still found to have some pronunciation errors. The study's findings underscore the role of social environment, interaction with others, and genetic predisposition in shaping a child's phonological development.